Gastrointestinal imaging - Levy, Angela D.; Mortele, Koenraad J.; Yeh, Benjamin ([New York] : Oxford University Press, 2015)
This volume presents a comprehensive review of gastrointestinal pathologies commonly encountered by practising radiologists and residents in training. The chapters are organised by organ system and include the pharynx and esophagus, stomach, small bowel, appendix, colon, anorectum, liver, gallbladder, bile ducts, pancreas, spleen, peritoneum, mesentery, and abdominal wall, and one on multisystem disorders. The book offers a guided approach to imaging diagnosis with examples of all imaging modalities complimented by the basics of technique and interpretation and the nuances necessary to reach the best diagnosis.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on September 8, 2015).
Keywords: Gastrointestinal system -- Imaging